(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
This research studies the principle of the work of laser sapphire and its development mechanism to obtain a high-energy pulse laser where the intensity of pulse and intensity of its electric field can be reached when the pulse is out of the laser. And then measure and calculate all parameters of this laser are: the length of the wave , frequency , the energy of a photon , the number of photons of one pulse, pulse capacity , intensity of pulse and intensity of electric field . Hence, study the spectral lines of the plasma generated by changing the gas medium surrounding the target material, and determine the displacement constants of the resulting spectral lines. The spectral lines are then studied by varying the radiation energy density of the laser pulse used, and its relation to the absolute temperature of the plasma. As the result of this study, the parameters widening and shifting of spectrum liens and the concentration of electrons in plasma had been calculated. Finally, the relative and absolute relativities measured in measured physical quantities were calculated.